IMPLIKASI MEKANISME CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN INTELLECTUAL CAPITAL - Elsafira Mala Anggeline; Novita Novita (Jurnal Akuntansi Trisakti, 2020)
This study aims to determine the effect of corporate governance mechanisms, such as the number of board of directors, the proportion of independent commissioners, and the largest share ownership of intellectual capital disclosure. This study uses two control variables, namely leverage and profitability. The population in this study is all property and real estate companies listed on the Indonesia Stock Exchange in 2015-2018. The sample used in this study was 124 property and real estate companies listed on the IDX in 2015-2018 using the purposive sampling method. Intellectual capital disclosure is done using the content analysis method. Data analysis in this study using the program STATA 15.1. The statistical method uses multiple linear regression analysis, by testing the statistical test hypothesis t. The results of this study indicate that the number of board of directors, the largest share ownership and leverage control variables influence the intellectual capital disclosure. While the variable proportion of independent commissioners and profitability does not affect intellectual capital disclosure.